Pengaruh Militer Dalam Sistem Politik Myanmar Terhadap Diskriminasi Etnis Rohingya Pada Tahun 2017 - Hardi Alunaza; Bastian Andhony Toy (Jurnal Ilmiah Hubungan Internasional, 2019)
This paper aims to discuss the extent to which the influence of the military in the political system in Myanmar related to cases of prosecution of ethnic Rohingya in 2017. Myanmar's government through the military is considered to use violence and discrimination against Rohingya ethnic groups resulting in thousands of casualties and the ethnic Rohingya fled to neighboring countries. This research was conducted to assess the role of the military in the Myanmar government system because under the 2008 Constitution, the military had a seat of 25 percent in the Myanmar parliament and had a number of authorities in the political system. This can be considered as a trigger for the military's aggressiveness towards Rohingya because of military representatives who have existence in the Myanmar parliament. The author uses concordance theory and the concept of new professionalism of internal security and national development in analyzing related phenomena. The results of this study indicate the existence of military influence in the Myanmar government because under the constitution, the military controls three strategic departments, namely Defense, Internal Affairs and Border. The military also holds full control of the armed forces, police and security forces, thus demonstrating the military role in Myanmar's policies regarding prosecution of the ethnic minority Rohingya.